Could Environmental, Social And Governance (ESG) And Halal Practices Be Converged? Preliminary Evidence Based On Integrated Reporting And Sustainability Reporting Of A Halal-certified Company - Nathasa Mazna Ramli; Nurul Nazlia Jamil; Dato' Hasnah Hj Haron; Aimi Nurshahirah Shahrul Kamil (Usim Press, 2024)
Indexed by Scopus